Prescribing errors in a Brazilian neonatal intensive care unit - Machado,Ana Paula Cezar (2015)
Abstract Pediatric patients, especially those admitted to the neonatal intensive care unit (ICU), are highly vulnerable to medication errors. This study aimed to measure the prescription error rate in a university hospital neonatal ICU and to identify susceptible patients, types of errors, and the medicines involved. The variables related to medicines prescribed were compared to the Neofax prescription protocol. The study enrolled 150 newborns and analyzed 489 prescription order forms, with 1,491 medication items, corresponding to 46 drugs. Prescription error rate was 43.5%. Errors were found in dosage, intervals, diluents, and infusion time, distributed across 7 therapeutic classes. Errors were more frequent in preterm newborns. Diluent and dosing were the most frequent sources of errors. The therapeutic classes most involved in errors were antimicrobial agents and drugs that act on the nervous and cardiovascular systems.